Algorithmic Management in the Food-Delivery Sector – a Contested Terrain? - Philip Wotschack; Leon Hellbach; Florian Butollo (Weizenbaum Journal of the Digital Society, 2024)
Forms of algorithmic management (AM) play an essential role in organizing food-delivery work by deploying artificial intelligence-based systems to coordinate driver routes. Given the risks of precarity and threats posed by AM, which are typically related to (migrant) platform work, the question arises to what extent structures of co-determination can positively shape this type of work and the technologies involved. Based on an in-depth case study within a large food-delivery company, this article is guided by two questions: (1) How do companies use algorithm-based management and performance control, and how do the couriers perceive them? (2) What priorities, strategies, resources, and achievements do works councils and trade unions have with regard to co-determination practices? Our analyses indicate that algorithmic management poses problems of non-transparency and information asymmetry, which in turn call for new forms of and procedures for co-determination. Our study does not find evidence that AM practices aim to individually profile and discipline couriers. The main challenges for the works council and trade unions arise from the couriers' generally precarious working and employment conditions; data- and AM-related issues do not represent the central area of conflict. However, our study identifies new demands regarding the co-determination of AM and underlines the importance of institutional regulation at the legal and sectoral level.
Keywords: 330; algorithmic management; platform work; AI regulation; co-determination; regulation; precarity